2016
DOI: 10.7717/peerj.1949
|View full text |Cite
|
Sign up to set email alerts
|

A novel multilocus variable number tandem repeat analysis typing scheme for African phylotype III strains of theRalstonia solanacearumspecies complex

Abstract: Background. Reliable genotyping that provides an accurate description of diversity in the context of pathogen emergence is required for the establishment of strategies to improve disease management. MultiLocus variable number tandem repeat analysis (MLVA) is a valuable genotyping method. It can be performed at small evolutionary scales where high discriminatory power is needed. Strains of the Ralstonia solanacearum species complex (RSSC) are highly genetically diverse. These destructive pathogens are the causa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 52 publications
2
27
1
Order By: Relevance
“…It is important that all these studies analyzed the genetic diversity in areas that were larger than ours (continent, country, and regional scales, respectively). Interestingly, our values were higher than that reported for an R. pseudosolanacearum phylotype III field population sampled in Cameroon (H E ϭ 0.03; G/N ϭ 0.235) (52). An explanation for the low genetic diversity detected, apart from a possible sampling bias effect, might be that the RSSC is capable of surviving in plants and in soil in a viable but not cultivable (VBNC) state (58).…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations
“…It is important that all these studies analyzed the genetic diversity in areas that were larger than ours (continent, country, and regional scales, respectively). Interestingly, our values were higher than that reported for an R. pseudosolanacearum phylotype III field population sampled in Cameroon (H E ϭ 0.03; G/N ϭ 0.235) (52). An explanation for the low genetic diversity detected, apart from a possible sampling bias effect, might be that the RSSC is capable of surviving in plants and in soil in a viable but not cultivable (VBNC) state (58).…”
Section: Discussioncontrasting
confidence: 53%
“…within the Ivory Coast and Africa (41), addressed the global surveillance of phylotype III (52), and identified sources of contamination of the Thames by phylotype IIB-1 (17). These studies improved the comprehension of RSSC epidemiology, its spread, its structuration on different scales, and its colonization pattern.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, in Cameroon and Ivory Coast, phylotypes I, II and III have been reported (Mahbou et al, 2009;N'Guessan et al, 2012) while in Ethiopia phylotypes I and II have been identified (Lemessa and Zeller, 2007). Phylotype I was also previously reported in Madagascar and eastern African countries bordering the Indian Ocean including Kenya and South Africa (Wicker et al, 2012;Ravelomanantsoa et al, 2016;Carstensen et al, 2017). This is the first report of phylotype IV in Kenya which could have been introduced in the country through imported potato seed with latent infection (Kaguongo et al, 2010).…”
Section: Discussionmentioning
confidence: 72%